Implementation of the Country Strategic Plan (CSP) by the World Food Program (WFP) for Pakistan in 2018 – 2022: Management Approach-Based Analysis - Devinta Permata Anggraeni; Resa Rasyidah (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2024)
This research aims to determine how the World Food Program (WFP) implements the realization of food security in Pakistan. The author used the management approach as an analytical reference that includes four approach methods related to the policy implementation process of the Country Strategic Plan (CSP) 2018 – 2022 implemented by WFP in Pakistan. These four methods include monitoring, stakeholder engagement, capacity building, and humanitarian assistance as a manifestation of the implemented CSP program. In this research, continuity was found in what WFP has done in Pakistan in mitigating the food crisis in the period 2018 – 2022. The monitoring that has been implemented comes from five methods of collecting information in the form of domestic, external, and internal reports from WFP Pakistan. Stakeholder engagement in the form of collaboration between IGOs and other NGOs. Capacity Building is manifested through strategic outcomes as the essence of the Country Strategic Plan (CSP) program. Humanitarian Assistance that has been provided materially and immaterially.